Particle Board from Chir Pine Needle - Nath, S. K.; Mohandas, K. K. (Indian Forester, 2014)
Chir pine needles are modified leaves from chir pine (Pinus roxbughii) trees, a major species in the temperate Himalayan forests. Under the present work, pine needles were used as raw material for making particle boards. Pine needle in its natural form is difficult to process and bond with conventional resin polymer into panel product. The nonporous surface of the needle is difficult to wet by resin. These problems were solved by cutting the needle into smaller sizes and bonding was improved by using specially made cardanol-phenol-formaldehyde resin. Glued and dried pine needles were drawn into mat and hot pressed to get panel products for various end uses. Process parameters varied to optimize strength properties of the products. Particle board made out of pine needles conforms to all properties of wood Particle Board as per IS: 3087 except MOR and MOE. Ceiling tiles of various designs were developed from glued pine needle as well as pulverized pine needle powder. Pine needle particle board (plain and design) was used as panel door infill and small tea-poy top to demonstrate the application potential.